Doing the Organization’s Work—Transcription for All Practical Governmental Purposes - Holder, Alex; Elsey, Christopher; Kolanoski, Martina; Brooker, Phillip; Mair, Michael (Frontiers in Communication, 2022)
By comparing two distinct governmental organizations (the US military and NASA) this paper unpacks two main issues. The paper examines the transcripts that are produced as part of the working activities in these worksites and what the transcripts reveal about the organizations themselves. In addition the paper analyses what the transcripts themselves display about the practices involved in their creation and use for practical purposes in these organizations. These organizations have been chosen as transcription forms a routine part of the worksites. Further, the everyday working environments in both organizations involve complex technological systems, as well as multiple-party interactions in which speakers are frequently spatially and visually separated. In order to explicate these practices, the article draws on the transcription methods employed in ethnomethodology and conversation analysis research as a comparative resource. In these approaches audio-video data is transcribed in a fine-grained manner that captures temporal aspects of talk, as well as how speech is delivered. Using these approaches to transcription as an analytical device enables us to investigate when and why transcripts are produced by the US military and NASA, as well as what is re-presented in the transcripts. By analysing these transcription practices it becomes clear that these organizations create huge amounts of audio-video ‘data’ about their everyday activities. One major difference between them is that the US military selectively transcribe this data (usually for the purposes of investigating incidents in which civilians might have been injured), whereas NASA’s ‘transcription machinery’ captures all aspects of mission-related interactions. As such the paper adds to our understanding of transcription practices within these organizations and how this is related to their internal accounting and transparency practices. The article also examines how the original transcripts have been used by researchers (and others) outside of the organizations themselves for alternative purposes.